The Radiation Dose Measurement of the Computed Tomography Scan to Ensure the Safety for Medical Staff in Dr. Sardjito General Hospital, Yogyakarta, Indonesia (Global Journal of Medical Research, 2017)
Abstract not found
Keywords: computed tomography; dose rate; inter-national commission on radiological protection